If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3-5n)-7(5+n)+3=0
We add all the numbers together, and all the variables
4(-5n+3)-7(n+5)+3=0
We multiply parentheses
-20n-7n+12-35+3=0
We add all the numbers together, and all the variables
-27n-20=0
We move all terms containing n to the left, all other terms to the right
-27n=20
n=20/-27
n=-20/27
| 3-4x=7x-1 | | 5x-12=3x+13 | | 16-4u=0 | | 5(x-3)=2(2x+6) | | 5(4x/3)=135 | | .06(n-450)=105 | | 70y-6=7 | | 5(11x-)=155 | | f(-3)=-3^2-5(-3)+36 | | 5(11x-)=-28 | | 5x-4=4x-10 | | 3x-11+5x/2=0 | | 6x-3=9x-24 | | 10x=-32-6 | | 7(4x+3)=27x+37 | | 6x-11-7=6(x-3) | | 3−7⋅3+4x=-18 | | 2x+1.9=4.1x+1.27 | | 3.6x-8.4=9.6 | | 2x+2(7-3x)=21 | | F(x)=-2x-5x+7 | | 3x^2+33x-8.1=0 | | 20/13=60/d | | -3x-9=5x+7 | | 12x-48=3x-3 | | 3m+7=97 | | 12x-48=3x-4 | | 7x-4=4x+5= | | x+8/3=x+2/3 | | 7×4=4x+5 | | 2+6x=-2x+10 | | 3x/5+7=2x/6+9 |